Tiertransporte in der Schweinehaltung: Führen mehr Informationen und Wissen bei Verbrauchern zu einer positiveren Einstellung?; Transportation in Pig Husbandry: Does an Increase in Consumers' Information and Knowledge Lead to a More Positive Attitude? - Stefan Clemens Wille; Gesa Busch; Achim Spiller (German Journal of Agricultural Economics (GJAE), 2017)
– In the European Union, and Germany in particular, the transport of livestock is an essential step in the meat production process. Pig transport especially, has frequently been the focus of public interest. In the last several decades, awareness for animal welfare has grown in society, which has often led to negative attitudes from the public towards farm animal husbandry and transportation. It is a well-known fact that a person's knowledge and his/her attitude are strongly linked. Thus far, the connection between knowledge and attitude with regards to the transport of farm animals, especially pigs, has not been scientifically examined. In an online survey taken by 272 German consumers the effect that additional information in the form of written texts and pictures on public perception was examined. The results of this study reveal that this additional information does have a positive effect on the respondents' attitudes, yet consumer attitudes remain rather negative.
Keywords: 330